Influence of mill type on densified biomass comminution. (15th November 2016) - Williams, Orla; Newbolt, Gary; Eastwick, Carol; Kingman, Sam; Giddings, Donald; Lormor, Stephen; Lester, Edward
Highlights: Comminution of wide range of densified biomass in four mills. Shape factors do not change significantly compared to particle size with milling. Shape will only noticeably change below the critical particle size for comminution. Mill choking linked to the particle size, shape and classifier Stokes condition. Classification requirements should inform biomass pellet particle sizes. Abstract: The impact of different mill fracture mechanisms were examined for a wide range of densified biomass pellets to provide a comprehensive analysis of biomass milling behaviour for pulverised fuel combustion. The milling behaviour of 7 woody, herbaceous, fruit, and thermally treated densified biomasses were investigated for four distinct types of comminution fracture mechanism using traditional milling indices and novel application of 3D imaging techniques. For the coal mill trials, a reference coal was used to provide a milling performance comparator. For the pre-milled samples, woody and herbaceous pellets have the least spherical particles (φ 0.324–0.404), followed by thermally treated pellets (φ 0.428), La Loma coal (φ 0.503), with olive cake having the most spherical particles (φ 0.562). This trend was noted for all the shape factors. Conventional comminution did not significantly impact biomass particle shape, even after a significant change in particle size. Therefore biomass pellet process history plays a key role in determining the comminuted particle shape. La Loma coal had significantly enhanced milling performance in comparison to the biomasses in the coal mills. Significant improvements in grindability and shape factors were observed for the thermally treated pellets. Mill choking was experienced for several of the woody and herbaceous samples, which resulted in a significant energy penalty. The mechanisms of mill choking were found to be intrinsically linked to the critical particle size of comminution through compression, particle shape factors, and the Stokes conditions set for the classifier and burners in pulverised fuel combustion systems. The study showed that for optimal milling performance, biomass pellets should be composed of particles which meet the Stokes requirements of the mill classifier. This would minimise the potential for mill choking and milling energy penalties, and ensure maximum mill throughput.